Penerapan Metode Design Thinking dalam Website Waste4Change untuk Mengoptimalkan Fitur Pengiriman Sampah - Ade Suryadana; Dimas Sasongko; Setiya Nugroho (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The The large population and daily activities of Indonesian people can trigger an increase in waste production. Proper waste management efforts require the role of all parties such as the government, the community, and even the support of the private sector in order to be able to overcome problems related to waste. One of the private parties that plays a role in waste management in Indonesia is Waste4Change. This company provides services and services related to waste transportation, waste recycling, as well as waste management education and consultation. These services can be accessed online through the website owned by Waste4Change. Based on the website, there are several programs and features that can be used by users, one of which is the Send Your Waste program. However, in the program, there is a waste delivery flow which has drawbacks, namely flow mismatch and copywriting on the Send Your Waste page. Therefore, this study aims to improve and develop the waste delivery flow in the Send Your Waste program to make it more user-friendly for users. The research method used is the design thinking method to find out what are the complaints and needs of users regarding the experience and appearance of the website interface. This method was chosen because it can solve complex problems with empathy to understand the needs and motivations of users and there is also an iterative process in order to find the best design solution. From the results of usability testing on experience and interface appearance, an increase in user satisfaction was found. With these improvements, it is concluded that the results of usability testing from the Waste4Change website can be accepted by users.